HUBUNGAN TINGKAT PENGETAHUAN DAN KETERAMPILAN DENGAN APLIKASI PENGISIAN PARTOGRAF OLEH MAHASISWA TINGKAT II SEMESTER IV KEBIDANAN WIRA HUSADA NUSANTARA MALANG INDONESIA - Nudhira, Uyunun; Astutik, Vivin Yuni; Sutriyani, Titin (Jurnal EDUNursing, 2017)
Abstract Partograf is very important monitoring for maternal labour. Most of pregnant, maternity and childbirth mortality can be prevented with monitoring partograf. This aims of this study to identify correlation between knowledge and skill midwefery student with partograf aplication.This research method is analytical survey, cross sectional study with porposive sampling 33 students.  The analytical method used in this research is multiple linear regression. The results showed that the level of knowledge and skills together affect with applications partograf obtained FValue = 228.213> F table = 3.32. squared multiple correlation R² is now equal to 0.938 (93.8%), and all of the variables are significant by the t tests As for the effect of each variable. Independently is a value Thitung level of knowledge (X1) = 3.100> Ttabel = 2.042 and Thitung skills (X2) = 5.787> Ttabel = 2.042. From the results of the independent variables are known Tvalue most dominant influence is a skill (X2) it can be seen from Tvalue> Ttabel other variables.knowledge and skill influancing with partograf aplication. From the results of the independent variables are known Tvalue most dominant influence is a skill (X2) it can be seen from Tvalue> Ttabel other variables. Key word: Knowledge, Skills, Filling Partograf